2014
DOI: 10.1002/ejhf.210
|View full text |Cite
|
Sign up to set email alerts
|

Impact of worsening renal function related to medication in heart failure

Abstract: Aims Renal failure is a major challenge in treating heart failure (HF) patients. HF medication may deteriorate renal function, but the impact thereof on outcome is unknown. We investigated the effects of HF medication on worsening renal function (WRF) and the relationship to outcome. Methods and results This post‐hoc analysis of TIME‐CHF (NT‐proBNP‐guided vs. symptom‐guided management in chronic HF) included patients with LVEF ≤45% and ≥1 follow‐up visit (n = 462). WRF III was defined as a rise in serum creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 40 publications
3
34
0
Order By: Relevance
“…29, 30 Further contributing to potential renal damage are recurrent episodes of acute kidney injury 31 and potential direct nephrotoxicity of medications received during the course of HF. 32 Much less is known about the effects of HF on long-term kidney function in patients with normal eGFR, but the above mentioned pathophysiologic changes postulated to cause poorer renal outcomes in those with preexisting CKD could also be instrumental in engendering new onset kidney damage and incident CKD. It is thought that the elevated renal G-Protein Coupled Receptor – G protein βγ (GPCR-Gβγ) signaling and endothelin system expression seen in heart failure may cause renal tissue damage, fibrosis and inflammation, which can manifest as acute renal failure and cardiorenal syndrome 2.…”
Section: Discussionmentioning
confidence: 99%
“…29, 30 Further contributing to potential renal damage are recurrent episodes of acute kidney injury 31 and potential direct nephrotoxicity of medications received during the course of HF. 32 Much less is known about the effects of HF on long-term kidney function in patients with normal eGFR, but the above mentioned pathophysiologic changes postulated to cause poorer renal outcomes in those with preexisting CKD could also be instrumental in engendering new onset kidney damage and incident CKD. It is thought that the elevated renal G-Protein Coupled Receptor – G protein βγ (GPCR-Gβγ) signaling and endothelin system expression seen in heart failure may cause renal tissue damage, fibrosis and inflammation, which can manifest as acute renal failure and cardiorenal syndrome 2.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Vardeny et al [21] demonstrated a favorable effect of spironolactone on survival in HF patients with reduced eGFR despite worsening renal function. On the other hand, worsening renal function following the use of high-dose loop diuretics was associated with increased mortality [24]. Given the beneficial effect of spironolactone on survival in HF patients despite decreased eGFR, one could hypothesize that some reduction in renal function with spironolactone should be accepted and should not lead to discontinuation of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in the setting of heart failure with reduced ejection fraction (HFrEF), the treatment benefits of the neurohormonal blockers strongly outweigh the accompanying WRF, which itself is more an intra‐renal haemodynamic reflection of neurohormonal blockade and not necessarily a signal of direct renal injury (pseudo‐WRF) . Yet, misinterpretation of these changes still results in inappropriate discontinuation of decongestive or neurohormonal blocker therapy in clinical practice . Paradoxically, patients with baseline CKD (who are at higher risk for WRF) might actually benefit the most in absolute terms of treatment with neurohormonal blockers, as the presence of CKD is associated with a higher event rate …”
Section: Prognostic Impact and Terminology Of Renal Functionmentioning
confidence: 99%
“…Despite the direct epidemiologic link between changes in renal function and outcome, a thorough knowledge on the pathophysiologic contributors of renal function changes during AHF is essential. Not all changes in eGFR are equal, and appropriate interpretation is essential to improve heart failure care …”
Section: Renal Function In Acute Heart Failurementioning
confidence: 99%
See 1 more Smart Citation